CHINESE CONSUMERS' BRAND LOYALTY FOR CONSUMER PRODUCTS: IMPORTANCE OF BRAND PERSONALITY AS MAJOR ANTECEDENT OF BRAND LOYALTY - Renee B. Kim,; Monica Zhao, (Asian Academy of Management Journal, 2014)
Brand personality has been viewed as an efficient means of distinguishing a brand from its competitors, thereby enhancing the effectiveness of advertising and marketing communications. Given the high potential usability of this method for marketers and brand managers, the current study investigates the determinant roles of brand personality on Chinese consumers' brand preferences. This study conceptualises and investigates the impact of brand personality on Brand Trust, Brand Affect, and Brand Loyalty. The overall findings indicate that different brand personality dimensions influence Brand Trust and Brand Affect in different ways, which in turn may increase the level of Brand Loyalty. The Sincerity dimension of brand personality was found to have a greater impact on the level of Brand Trust than on Brand Affect, while the other four dimensions (Excitement, Competence, Sophistication and Ruggedness) of brand personality were found to have a greater influence on Brand Affect. In addition, Brand Affect was found to have a substantially greater effect on Brand Loyalty than Brand Trust across all five Brand Personality dimensions.